OPTIMIZATION OF COLLIMATOR NEUTRON DESIGN FOR BORON NEUTRON-CAPTURE CANCER THERAPY (BNCT) BASED CYCLOTRON 30 MeV - Aniti Payudan; Aris Haryadi; Farzand Abdullatif (Indonesian Journal of Physics and Nuclear Applications, 2017)
This research in BNCT has a goal to design a collimator that can be used for cancer therapy. Simulations were carried out by MCNPX software. A collimator is designed by cyclotron 30 MeV as a neutron generator. Independent variables varied were material and thickness of each collimator’s component to get five of IAEA’s standard of the neutron beam. The result is two collimator designs that can pass all IAEA’s standard. Those designs are cyclotron collimator I and cyclotron collimator II. Collimator designs obtained are tube collimator consisting of a cylindrical target 7Be length of 1.4 cm and radius 1 cm, a lead wall with thickness 23 cm, cylindrical heavy water moderator (D2O) with radius 3 cm. Filter Cd-nat for cyclotron collimator I with a thickness of 1 mm and a radius 3 cm. Cyclotron collimator II uses 60Ni with a thickness of 5 cm as a filter. The radius aperture is 3 cm. These two collimator designs can be used for cancer treatment with BNCT. Dosimetry calculation and manufacture of prototypes are needed to test the application of this design.